An Evolutionary Review of the Technology Adoption Models - Rao, O. R. S., Joydeep Mookerjee, Subir Chattopadhyay (Mathematical Statistician and Engineering Applications, 2022)
The use of information systems and modern technologies is crucial for any business nowadays. Thus, several models and hypotheses concerning the acceptability of technological innovations have emerged. Several models were discovered via research to introduce the aspects contributing to the information system’s success. The researchers examined and evaluated 15 models and theories of technology adoption at the individual level through a theoretical lens grounded in the literature. Throughout the assessment, the models that rely heavily on assumptions are highlighted. The present study will summarize the weaknesses and virtues of these models and ideas.